Climate Information in Retail Investors' Decision-Making: Evidence From a Choice Experiment. (March 2019) - Bassen, Alexander; Gödker, Katrin; Lüdeke-Freund, Florian; Oll, Josua
Financial markets play a decisive role in the transition to a low-carbon economy. This study investigates the role of climate information presentation for climate-friendly investing among retail investors. We conduct a choice experiment in which we vary the presentation format of climate information by means of three label designs to test their influence on investment practices. We provide empirical evidence for the effectiveness of climate labeling as a potential nudge for climate-friendly investing. Furthermore, we find heterogeneity in the influence of climate information across different label designs and cognitive characteristics of investors. Intuitive (reflective) decision makers tend to place significantly more (less) weight on funds' climate performance compared with financial performance—irrespective of a participant's environmental preference.